Exploring intrusive experiences in older people across the spectrum of worry - Miller, Emma Frances (The University of Edinburgh, 2014)
Background: Worry is theorised to function as a form of cognitive or experiential avoidance wherein an individual uses repetitive thinking in an attempt to avoid a future event or an aversive internal experience. There is evidence of a closer link between non-verbal thought (e.g. mental images) and emotion, physiology and behaviour than with verbal thought. Based on findings that worry is predominantly a verbal-linguistic activity, with less imagery occurring during worry episodes than during relaxation; it is theorised that worriers may move from non-verbal to verbal thought in order to avoid the greater arousal associated with non-verbal thought intrusions. This carries with it the unintended consequence of reducing emotional processing, leading to a subsequent increase in intrusive thoughts. Whilst cognitive science has emphasised the content of cognition and how this links to emotion, the psychological flexibility model suggests that content is less important than how we relate to our cognitive events. The degree to which we get entangled in our thinking, lack perspective on our thoughts and the degree to which cognition comes to regulate our behaviour over other sources is known as cognitive fusion. It is postulated that some individuals may be more prone to avoiding internal experiences due to the stance they take toward these experiences. In the long-term, worry should lead to a reduction in the experience of intrusive images and memories and an increase in intrusive thoughts; and this relationship should vary depending on an individual’s stance in relation to their internal experiences. The purpose of the current study is to explore the experience of intrusive memories, images and thoughts in an older adult sample, and the relationship of these experiences to level of worry, cognitive fusion and psychological inflexibility. Method: Sixty-two community dwelling older adults were involved in the study. Each completed questionnaire measures to assess level of trait worry, depression, cognitive fusion and psychological inflexibility, as well as an interview to determine whether diagnostic criteria were met for any mood or anxiety disorder and to complete an interview exploring the experience of intrusive memories, thoughts and images. Findings: Higher levels of trait worry were strongly associated with higher levels of cognitive fusion and psychological inflexibility. Intrusive memories, images and thoughts were all reported in low levels across the sample. Level of worry was positively associated with the severity but not the occurrence of intrusive memories and thoughts. Higher levels of psychological inflexibility were associated with less occurrence of intrusive memories and images; whereas higher levels of cognitive fusion were associated with the increased occurrence of intrusive images. Higher levels of worry, cognitive fusion and psychological inflexibility were all associated with increased severity of intrusive thoughts. The findings are discussed in relation to previous research and to the Avoidance Theory and Acceptance Model of GAD. Implications are considered for further research and clinical applications.
Keywords: older people; images; worry; memories; intrusions; thoughts